2012
DOI: 10.1177/1071181312561261
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of slipping on lumbar muscle activity, kinematics, and kinetics

Abstract: Slips, trips, and falls remain leading causes of occupational injuries and fatalities. The current exploratory study quantified lumbar kinematics and kinetics during both induced slips and normal walking. Individual anthropometry, lumbar muscle geometry, and lumbar kinematics, along with electromyography of 14 lumbar muscles were used as input to a 3D, dynamic, EMG-based model of the lumbar spine. Results indicated that, in comparison with values during normal walking, lumbar kinematics, lumbosacral kinetics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Of note, comparing our findings reported herein to our earlier study (Rashedi et al, 2012), both compression and shear forces were estimated to be somewhat smaller, likely due to protocolrelated differences in conducting the experiment, including the material used to make the surface slippery.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Of note, comparing our findings reported herein to our earlier study (Rashedi et al, 2012), both compression and shear forces were estimated to be somewhat smaller, likely due to protocolrelated differences in conducting the experiment, including the material used to make the surface slippery.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, increased L5/S1 moments were found when recovering from slip events simulated via platform displacements during load carriage (Liu et al, 2014). Rashedi et al (2012) reported pilot results (n = 6) on lumbar responses to an unexpected slip, which suggested higher lumbar muscle forces, along with higher L5/S1 reaction moments and internal forces (i.e., compression and shear forces), compared to those found during unperturbed gait.…”
Section: Introductionmentioning
confidence: 97%